2017
DOI: 10.1108/he-05-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ perceptions of alcohol

Abstract: Purpose Rising trends in alcohol consumption and early drinking initiation pose serious health risks especially for adolescents. Learner’s prior knowledge about alcohol gained from the social surroundings and the media are important sources that can impact the learning outcomes in health education. The purpose of this paper is to map adolescents’ perceptions of alcohol in Punjab, India and how these perceptions are related to their attitudes towards their social surroundings and the media. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…nursing students K 70% had inadequate knowledge of human rights related to mental illness Ram et al, 2017 [ 54 ] Suicide 339 (U) 17–31 (21.80 ± 2.18) 68.7 Mysuru, Karnataka Undergraduate, postgraduate and interning medical students and paramedical students KA 36% were unable to identify symptoms of depression; 64% felt that talking about suicide increases risk of suicide, 62% more men commit suicide than women; 65% happens to few people; 52% of people with depression need to be hospitalized. 45.42% would not disclose suicidal ideation; 49.55% - people with mental illness change their mind quickly Roy et al, 2017 [ 55 ] Substance use 379 (U) 13.6 NR Patiala, Punjab Nr KA 19% did not know that alcohol is a drug. 22% assumedthat smaller doses of alcohol do no harm.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…nursing students K 70% had inadequate knowledge of human rights related to mental illness Ram et al, 2017 [ 54 ] Suicide 339 (U) 17–31 (21.80 ± 2.18) 68.7 Mysuru, Karnataka Undergraduate, postgraduate and interning medical students and paramedical students KA 36% were unable to identify symptoms of depression; 64% felt that talking about suicide increases risk of suicide, 62% more men commit suicide than women; 65% happens to few people; 52% of people with depression need to be hospitalized. 45.42% would not disclose suicidal ideation; 49.55% - people with mental illness change their mind quickly Roy et al, 2017 [ 55 ] Substance use 379 (U) 13.6 NR Patiala, Punjab Nr KA 19% did not know that alcohol is a drug. 22% assumedthat smaller doses of alcohol do no harm.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies included college students pursuing other disciplines [ 35 , 58 , 60 ]. Four secondary school-based studies were found [ 44 , 55 , 56 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Roy et al (2017) demonstrated that about half of all respondents (school students) were willing to follow advice from their favorite celebrity. They also suggested that such endorsements increase the likeability and credibility of the brands among users and potentially increase brand sales [ 50 ]. This is likely the reason that references to celebrity endorsement were seen for a few brands in both countries.…”
Section: Discussionmentioning
confidence: 99%